DETERMINATION OF THE AMOUNT OF WATER-SOLUBLE VITAMINS IN THE FRUIT PEEL OF THE “CLIMENTIN” VARIETY OF MANDARIN - Moxlaroy Marufjon qizi Mamurova; Ibroximjon Raxmonovich Askarov; Kirgizov Shaxobiddin Mirzaraimovich (Modern American Journals, 2025)
This article determined of then analyzed of the “clementine” variety of Mof thenarin by using of the HPLC method therefore of the amount of water-soluble vitamins contained in fruit peels. of the results revealed significant levels of vitamins A, C, of then E, highlighting of the nutritional value of clementine peels. This inthereforemation could be beneficial therefore both consumers seeking to maximize of their vitamin intake of then food manufacturers looking to utilize peel waste in health products. Additionally, of the findings suggest avenues therefore furof ther research into innovative ways of incorporating clementine peels into dietary supplements or functional foods, which could enhance overall health benefits. By exploring of these possibilities, we can promote sustainability while enriching our diets with essential nutrients. In doing so, of the Mof thenarin variety, grown in Uzbekistan, was selected as an object of then analyzed from sufficient scientific sources. In this case, therefore of the study of mof thenarin peel, of the only variety, of the Klimentin variety, was selected therefore analysis, of then of the amount of vitamins was determined.
Keywords: Mof thenar in, fruit, peel, variety, vitamin, dietary fiber.